Pawpaw enriched soymilk beverage - Bolarinwa, IF; Aruna, TE; Ajetunmobi, RI; Adejuyitan, JA; Alawode, OW (Bangladesh Journal of Scientific and Industrial Research, 2021)
Effects of enriching soymilk with pawpaw puree at different ratios (10 – 40%) were evaluated for physicochemical properties, vitamin A and C, mineral contents, and sensory attributes. The results showed increase in total soluble solids (5.5 – 8.5 oBrix), total titratable acidity (0.53 – 0.87 g/kg) and viscosity (19.9 – 26.7 cp), but decreased in pH (7.4 – 6.8). Vitamin A and C contents of the soy-pawpaw beverage increased from 12.4– 20.4 μg/100 ml and 10.9 – 25.8 mg/100 ml, respectively. All the macromineral contents of the enriched soymilk beverages increased significantly except for sodium.Enrichment of soymilk with pawpaw puree improved the sensory attributes of the drink in terms of flavour, taste, mouthfeel and overall acceptance, especially at high supplementation level (40%). Soymilk with pawpaw puree resulted in products with better vitamin A and C and macro-mineral contents than plain soymilk drink, thus, the soy-pawpaw beverage will complement consumers micro and macro-nutrient intake. Bangladesh J. Sci. Ind. Res.56(2), 105-114, 2021